ANALISIS PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN (STUDI KASUS LAZISMU YOGYAKARTA) - Widianti, Emma; Fatimah, Naimah (Applied Research in Management and Business, 2024)
The role of employees in supporting the progress of a social institution like LAZISMU D.I. Yogyakarta is very important, particularly their emotional intelligence and spiritual intelligence, to be able to compete with other increasingly tight and competitive social institutions. In such a workplace environment, LAZISMU D.I. Yogyakarta employees are absolutely required to have high spiritual and emotional intelligence to ensure their performance is optimal. This study uses a quantitative method with primary data obtained from distributed questionnaires. The population in this study consists of employees working at LAZISMU D.I. Yogyakarta. The analysis technique used is multiple linear regression (T-test and F-test) to answer the hypotheses formulated by the researchers. The results of the study indicate that spiritual intelligence has a partial and significant effect on employee performance, as evidenced by the value of tcount > ttable (0.716 > 0.207) and a significance value of 0.480 (sig < 0.05). Meanwhile, emotional intelligence also has a partial and significant effect on employee performance, as shown by the value of tcount > ttable (0.514 > 0.207) and a significance value of 0.611 (sig < 0.05). Additionally, spiritual intelligence and emotional intelligence simultaneously affect employee performance, demonstrated by the value of Fcount > Ftable (0.045 > 3.195) with a significance value of 0.956. The independent variables (Spiritual Intelligence and Emotional Intelligence) can influence the dependent variable (Employee Performance) by 83%, as evidenced by an R Square value of 0.830, while the remaining 17% is influenced by other variables in the study.